FACTS AND OPINIONS ON USEFULNESS OF PNEUMOCOCCAL VACCINE - M.P. Kostinov; O.O. Magarshak; E.G. Belonogova ("Paediatrician" Publishers LLC, 2009)
The article describes the problem of pneumococcal infections (pneumonias, meningitis, otitis) in children and adults. The modern opportunities of vaccinoprophylaxis and its usefulness in public health service are shown. The perspectives and questions on safety and effectiveness of pneumococcal conjugated 7-valent vaccine as the basic method of pneumococcal infections prophylaxis in infants and children from risk groups (with bronchial asthma, sickle-cell anemia, etc.) are presented in details.Key words: children, pneumococcal infection, vaccination, pneumococcal conjugated 7-valent vaccine.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):79-83)